2021
DOI: 10.1111/1440-1681.13552
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of thyroid dysfunctions in adolescent patients suffering from severe acne during isotretinoin treatment

Abstract: Although oral isotretinoin has been widely used as a basic treatment of acne in adolescents, several studies have noted some alterations in thyroid functions during oral isotretinoin therapy. Therefore, the present study aims at evaluating the possible changes in thyroid‐stimulating hormone (TSH), free thyroxin (fT4) and free triiodothyronine (fT3) levels during isotretinoin treatment and analyzing the possible factors which may contribute to such changes. In the present study, 47 patients received (0.5 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Researchers have found that ISO treatment causes significant changes in hormone levels, thyroid gland hormones decrease and pituitary thyroid-stimulating hormone levels increase, and the observed changes in hormonal levels were increased with the augment of therapy. 75 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that ISO treatment causes significant changes in hormone levels, thyroid gland hormones decrease and pituitary thyroid-stimulating hormone levels increase, and the observed changes in hormonal levels were increased with the augment of therapy. 75 …”
Section: Resultsmentioning
confidence: 99%
“…Researchers have found that ISO treatment causes significant changes in hormone levels, thyroid gland hormones decrease and pituitary thyroid-stimulating hormone levels increase, and the observed changes in hormonal levels were increased with the augment of therapy. 75 Some scholars, such as Toossi et al 76 , proposed that ISO caused low serum vitamin D levels and that there was a correlation between acne and serum vitamin D deficiency. Shrestha et al 13 put forward the opposite view, they concluded that patients with moderate to severe acne had low vitamin D levels, that no change in vitamin D levels was found after short-term treatment with oral ISO, and that there was no significant association between acne and serum vitamin D deficiency.…”
Section: Other Reactionsmentioning
confidence: 99%